2004
DOI: 10.1002/micr.20034
|View full text |Cite
|
Sign up to set email alerts
|

Development of donor‐specific chimerism and tolerance in composite tissue allografts under αβ‐T‐cell receptor monoclonal antibody and cyclosporine a treatment protocols

Abstract: Recently, we induced donor-specific tolerance to rat hindlimb allografts under a 35-day course of alphabeta-T-cell receptor monoclonal antibody (alphabeta-TCR mAb) and cyclosporine A (CsA). In this report, we investigated the role of shorter alphabeta-TCR/CsA protocols on tolerance induction. We performed 52 hindlimb transplantations, between Lewis-Brown-Norway (LBN, F1) donors and Lewis recipients to test the impact of 21-, 7-, and 5-day protocols of combined alphabeta-TCR/CsA treatment on tolerance induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Tissue survival associated with donor-specific tolerance has only recently been satisfactorily demonstrated in studies that made use of rat hind limb and vascularized skin transplant models, monoclonal ab T-cell receptor antibodies, and a short course of either FK-506 or cyclosporine A [50][51][52] . Although mixed chimerism has been considered a promising method of tolerance induction, the method remains problematic for nonlife-critical transplants 53 .…”
mentioning
confidence: 99%
“…Tissue survival associated with donor-specific tolerance has only recently been satisfactorily demonstrated in studies that made use of rat hind limb and vascularized skin transplant models, monoclonal ab T-cell receptor antibodies, and a short course of either FK-506 or cyclosporine A [50][51][52] . Although mixed chimerism has been considered a promising method of tolerance induction, the method remains problematic for nonlife-critical transplants 53 .…”
mentioning
confidence: 99%
“…17 Next, we tested short-term protocol of combined ␣␤ T-cell receptor monoclonal antibody and cyclosporine A (␣␤-TCRmAb/CsA) for tolerance induction in semiallogenic and fully major histocompatibility (MHC) mismatched limb transplants. 18,19 In both models, limb transplants served as a source of VBMT, and indefinite survival and tolerance were confirmed by skin grafting and MLR assay.…”
mentioning
confidence: 99%
“…75,108 Furthermore, it was also shown that these mAbs decreased the expression of the TCR on the surface of the T cell. 109,110 Initial studies using anti-TCR mAbs on an experimental cardiac allograft model demonstrated that they abrogated accelerated rejection (in a hamster-to-rat model) and prolonged cardiac allograft survival in a dose-dependent fashion. 111 Recently, several studies used anti-TCR mAbs in CTA.…”
Section: Anti-tcr Mabsmentioning
confidence: 99%